Narratives of Mahdi bin Maimun al-Kurdi (died 172 AH) in Sunan al-Tirmidhi: Modern Analytical Study - Saleh, Khaled; Yahya, Farsat (Humanities Journal of University of Zakho, 2021)
The research seeks to study and translate the biography of the Kurdish character Hafiz Mahdi Bin Mamoon, who has a prominent and distinguished role to serve the Prophet’s hadith through his preservation and writings, in order to reveal his life by revealing his name, lineage and origin, and mentioning the names of his elders, students, culture and praise by scholars, as well as seeking to study analytical his novels in (Sinn al-Termadi) through the outcomes of hadiths, and the study of its origins,The statement of its judgment in many terms like health and vulnerability, the mention of the acne’s community, the meaning of the words, the reason that mention of the hadith if it has a reason, the explanation of the things and their doctrinal clarification, and the statement regarding its benefits.